Prevalence of helicobacter pylori in patients undergoing upper GI endoscopy in hospital No 1 Kerman university of medical sciences - H Jojaji (Journal of Kerman University of Medical Sciences, 1994)
Prevalence of helicobacter pylori was evaluated by urease test in 513 patients undergoing GI endoscopy, in hospital No1 Kerman university of medical sciences and health services from June 1992 through April 1993. H. Pylori was detected in 56.9℅ of tested samples by urease test. There was no significant correlation with sex, age and cigarette smoking. Prevalence of H.pylori was 16℅ in control group, 10℅ for esophageal varices, 20℅ for gastric ulcer, 22.58 for prepyloric ulcer, 67.22℅ for cancer, 29.55℅ for non-ulcer dyspepsia, 59.42℅ for duodenitis, 62.5℅ for prepyloric ulcer, 67.22℅ for and duodenal ulcer groups compared to control was higher( statistically insignificant). Prevalence of H.pylori in females suffering from duodenal ulcer was also higher than males( 91.43℅ compared to 72.41℅ respectively), and this difference was statistically significant.